$\dfrac{6x-2}{9}$ $+$ $\dfrac{3x+5}{18}$ $=$ $\dfrac{1}{3}$ is a given algebraic equation. It is actually defined only in one variable $x$ and its exponent is one. Therefore, the equation in algebraic form is known as linear equation in one variable.
$\dfrac{6x-2}{9}$ $+$ $\dfrac{3x+5}{18}$ $=$ $\dfrac{1}{3}$
In order to isolate $x$, the linear equation in one variable should be simplified and then it can be solved by using transposing method.
$\implies$ $\dfrac{6x}{9}$ $-$ $\dfrac{2}{9}$ $+$ $\dfrac{3x}{18}$ $+$ $\dfrac{5}{18}$ $=$ $\dfrac{1}{3}$
$\implies$ $\require{cancel} \dfrac{\cancel{6}x}{\cancel{9}}$ $-$ $\dfrac{2}{9}$ $+$ $\dfrac{\cancel{3}x}{\cancel{18}}$ $+$ $\dfrac{5}{18}$ $=$ $\dfrac{1}{3}$
$\implies$ $\dfrac{2x}{3}$ $-$ $\dfrac{2}{9}$ $+$ $\dfrac{x}{6}$ $+$ $\dfrac{5}{18}$ $=$ $\dfrac{1}{3}$
$\implies$ $\dfrac{2x}{3}$ $+$ $\dfrac{x}{6}$ $-$ $\dfrac{2}{9}$ $+$ $\dfrac{5}{18}$ $=$ $\dfrac{1}{3}$
$\implies$ $\dfrac{2 \times 2x + 1 \times x}{6}$ $+$ $\dfrac{5}{18}$ $-$ $\dfrac{2}{9}$ $=$ $\dfrac{1}{3}$
$\implies$ $\dfrac{4x+x}{6}$ $+$ $\dfrac{5}{18}$ $-$ $\dfrac{2}{9}$ $=$ $\dfrac{1}{3}$
$\implies$ $\dfrac{5x}{6}$ $+$ $\dfrac{1 \times 5 -2 \times 2}{18}$ $=$ $\dfrac{1}{3}$
$\implies$ $\dfrac{5x}{6}$ $+$ $\dfrac{5-4}{18}$ $=$ $\dfrac{1}{3}$
$\implies$ $\dfrac{5x}{6}$ $+$ $\dfrac{1}{18}$ $=$ $\dfrac{1}{3}$
$\dfrac{5x}{6}$ $+$ $\dfrac{1}{18}$ $=$ $\dfrac{1}{3}$
The linear equation in one variable is successfully simplified. Now, the transpose method can be applied for transposing the terms and it helps us to find the unknown.
In this case, the term $\dfrac{1}{18}$ should be transposed to right-hand side of the equation. It is a first step for isolating the $x$ in this linear equation problem.
$\implies$ $\dfrac{5x}{6}$ $=$ $\dfrac{1}{3}$ $-$ $\dfrac{1}{18}$
$\implies$ $\dfrac{5x}{6}$ $=$ $\dfrac{6 \times 1 -1 \times 1}{18}$
$\implies$ $\dfrac{5x}{6}$ $=$ $\dfrac{6-1}{18}$
$\implies$ $\dfrac{5x}{6}$ $=$ $\dfrac{5}{18}$
$\implies$ $6 \times \dfrac{5x}{6}$ $=$ $6 \times \dfrac{5}{18}$
$\implies$ $\dfrac{6 \times 5x}{6}$ $=$ $\dfrac{6 \times 5}{18}$
$\implies$ $\require{cancel} \dfrac{\cancel{6} \times 5x}{\cancel{6}}$ $=$ $\dfrac{\cancel{6} \times 5}{\cancel{18}}$
$\implies$ $5x$ $=$ $\dfrac{5}{3}$
$5x$ $=$ $\dfrac{5}{3}$
The role of transposing method is completed. Now, the root of the linear equation in one variable can be evaluated by the inverse operations method.
$\implies$ $\dfrac{5x}{5}$ $=$ $\dfrac{\dfrac{5}{3}}{5}$
$\implies$ $\require{cancel} \dfrac{\cancel{5}x}{\cancel{5}}$ $=$ $\dfrac{\dfrac{5}{3}}{\dfrac{5}{1}}$
$\implies$ $x$ $=$ $\dfrac{5}{3} \times \dfrac{1}{5}$
$\implies$ $x$ $=$ $\dfrac{5 \times 1}{3 \times 5}$
$\implies$ $x$ $=$ $\require{cancel} \dfrac{\cancel{5} \times 1}{3 \times \cancel{5}}$
$\,\,\, \therefore \,\,\,\,\,\,$ $x$ $=$ $\dfrac{1}{3}$
A free math education service for students to learn every math concept easily, for teachers to teach mathematics understandably and for mathematicians to share their maths researching projects.
Copyright © 2012 - 2023 Math Doubts, All Rights Reserved